Tripartite Institutional Mechanism in the Discussion of the Draft Law - Ari Wuisang; Roby Satya Nugraha (JURNAL AKTA, 2025)
This article explores the emergence and implementation of a tripartite institutional mechanism in the legislative process in Indonesia, particularly following the Constitutional Court Decisions No. 92/PUU-X/2012 and No. 79/PUU-XII/2014. These rulings affirm the legislative role of the Regional Representative Council (DPD) alongside the House of Representatives (DPR) and the President, establishing a more balanced representation in drafting laws within specific areas. Using a normative juridical approach, this study analyzes the constitutional foundations, institutional practices, and comparative perspectives on bicameralism. The research identifies significant structural and functional disparities between the DPR and DPD, despite the formal recognition of the DPD’s legislative rights. Although the DPD may participate in the first and second-level discussions of draft bills, it is excluded from the final approval stage. Moreover, DPD-initiated bills and proposed revisions are often ignored in practice, weakening its legislative impact. Drawing from comparative constitutional studies, the article highlights the typologies of bicameralism—ranging from perfect to weak—and situates Indonesia's model within the broader global context. The findings underline that a truly effective tripartite mechanism requires not only formal recognition but also practical and procedural adjustments to ensure power-sharing and institutional dignity. The authors recommend enhancing the DPD's authority through constitutional practices, internal institutional development, and greater political negotiation capacity to strengthen its legislative influence and create a more balanced parliamentary structure.